ANALISA FAKTOR PENYEBAB STRES DAN MANAJEMEN STRES PADA KEPALA SMA BAHRUL MAGHFIROH MALANG - Septiawan, Bambang (Jurnal al Hikmah, 2018)
Stress often occurs when doing work activities. This happens either because most work or time is tight to get it done. As the high school principal of Bahrul Maghfiroh, it was indicated that there was a stressful job from several levels. Therefore this is interesting to study because according to experts, someone who works in the education world is at the top of the stress level. This study uses descriptive qualitative methods and includes the phenomenology. Then, this study focuses on the factors of causes and managements. The results of this study indicate that the stressors of the head of SMA Bahrul Maghfiroh are the coming of tasks simultaneously in the near future as well as the double task that burdened him. Furthermore, stress management is done to form a priority scale, regular meetings, and do refreshing in the form of sports